Analisis kemampuan pemecahan masalah dengan menerapkan blended learning berbantuan edmodo - Shelly Rozalina; Nurdalilah Nurdalilah (Mahesa Research Center, 2022)
This study aims to analyze students' problem-solving abilities in solving problems on flat-sided geometric shapes by applying Edmodo-assisted blended learning. This research method uses qualitative methods with a descriptive approach. This study describes students' mathematical problem-solving abilities in the process of learning mathematics with the help of Edmodo. The subjects used in this research were class VIII-A students at MTsS Al-Washliyah Pulau Gambar, which currently consists of 20 students. The data collection used was in the form of math problem-solving ability tests and interviews. Based on the results of the study, which showed that the problem-solving abilities of students with the help of Edmodo were able to provide an understanding of the problems of questions on flat-sided geometric material, The results of the percentage of problem-solving abilities in the high-level category are 50%, the medium-level percentage is 25%, and the low-level percentage is 25%. To further strengthen the results, a sample of five students will be interviewed at various levels of ability. However, students showed a positive response to Edmodo-assisted learning media.